Pelatihan Karya Ilmiah bagi Guru Sejarah Kota Samarinda - Muhammad Azmi; Siti Marfuah (Carmin: Journal of Community Service, 2021)
In an effort to develop scientific works in the field of History education, it is necessary to increase the ability of teachers as history educators to obtain the latest information related to educational developments. The purpose of this activity is to provide history teachers with comprehensive information and descriptions of scientific publications for disseminating information related to classroom experiences. This activity was attended by 36 history teachers who are members of the subject teacher consultation of history in Samarinda. The limitation faced in this activity is that the implementation of the activity is only for history teachers in Samarinda City. In the future, the training will be further expanded, not only in Samarinda City, but also to history teachers in other areas. The input given by the participants to this activity is the factor of facilities and infrastructure available at the activity site. The activity room is very representative, but its location on the top floor makes some participants tired.